A miniaturized optical tomography platform for volumetric imaging of engineered living systems. Issue 4 (18th January 2019) - Polat, Adem; Hassan, Shabir; Yildirim, Isa; Oliver, Luis Eduardo; Mostafaei, Maryam; Kumar, Siddharth; Maharjan, Sushila; Bourguet, Louis; Cao, Xia; Ying, Guoliang; Eyvazi Hesar, Milad; Zhang, Yu Shrike
Abstract : Volumetric optical microscopy approaches that enable acquisition of three-dimensional (3D) information from a biological sample are attractive for numerous non-invasive imaging applications. Abstract : Volumetric optical microscopy approaches that enable acquisition of three-dimensional (3D) information from a biological sample are attractive for numerous non-invasive imaging applications. The unprecedented structural details that these techniques provide have helped in our understanding of different aspects of architecture of cells, tissues, and organ systems as they occur in their natural states. Nonetheless, the instrumentation for most of these techniques is sophisticated, bulky, and costly, and is less affordable to most laboratory settings. Several miniature imagers based on webcams or low-cost sensors featuring easy assembly have been reported, for in situ imaging of biological structures at low costs. However, they have not been able to achieve the ability of 3D imaging throughout the entire volumes for spatiotemporal analyses of the structural changes in these specimens. Here we present a miniaturized optical tomography (mini-Opto) platform for low-cost, volumetric characterization of engineered living systems through hardware optimizations as well as applications of an optimized algebraic algorithm for image reconstruction.